KONSEP RELATION INFERRED SELF EFFICACY DALAM AL-QUR’AN (TELAAH TAFSIR MAUDHU’I) - Siti Khumayroh; Nyoko Adi Kuswoyo; Amir Mahmud; Wiwin Ainis Rohtih (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2026)
This research is related to the Concept of Relationship Inferred Self Efficacy in the Qur'an. Where this concept has a great influence on the psychology of people with spinal disorders, namely scoliosis. Scoliosis is a spinal disorder that not only has an impact on the physical condition, but also on the psychological condition of the sufferer. Such as a decrease in confidence in one's ability or called Self Efficacy. From the perspective of social psychology, Albert Bandura explained that self-efficacy is not only formed by personal experience, but also influenced by social relations, known as the concept of Relation Inferred Self-Efficacy (RISE), which is an individual's belief in his or her own abilities formed from the perception of the judgment of others. Therefore, supportive relationships are an important factor in increasing the self-efficacy of people with scoliosis. This type of research has a library research nature with primary data sources from the Qur'an and uses the maudhu'i tafsir method, where this interpretation starts from collecting and analyzing verses of the Qur'an related to human characteristics and beliefs or faith. The purpose of this research is to find out how the concept of RISE can be understood in the perspective of the Qur'an and how the verses of the Qur'an provide a theological and psychological basis regarding the importance of social relations in building individual confidence and mental fortitude, especially for people with scoliosis. The results of the study show that the Qur'an emphasizes the importance of relationships based on compassion, empathy, good communication, and mutual strengthening, which is in line with the concept of RISE in Bandura's theory. Values such as advising each other, providing support, and strengthening others are factors that can increase individual self-efficacy. Thus, the Qur'an not only provides spiritual solutions, but also offers relevant psychosocial principles in an effort to increase self-efficacy through positive relationships.